Second hankel determinant for new subclass of analytic functions associated with q-derivative operator - Tseu, Suet Yie; Aini Janteng, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper utilizes the concept of subordination and q-derivative operator to introduce a new subclass of analytic functions in the open unit disk. The primary objective of this paper is to obtain the upper bounds for the second Hankel determinant for the functions belonging to this class.